(untitled) (Global Journal of Human-Social Science, 2017)
Financial constraints have driven K-12 schools in the isolated mountain regions of USA to reduce costs by shortening the teaching week. These regions have a high relative population of Hispanic Mexican immigrants who are English Language Learners (ELL). Hispanic immigrants come to USA to work but generally at low wages so it is a financial strain to pay childcare during the week to avoid losing a day of work. At the same time teachers are under pressure from the No Child Left Behind national initiative to ensure all students pass standardized tests. There is some evidence that shorter school weeks does not negatively impact student learning. However, we argue that a shorter school week negatively impacts ELL student performance on standardized exams, and if this were true it would be unfair to immigrants so the practice should be changed. We empirically tested the effectiveness of various school week formats using a large sample of rural schools in Oregon with a high concentration of ELL students from Hispanic Mexican cultures (N=628).